How online grocery shopping alters food-related consumer behavior - Šarkovská, Klára; Chytková, Zuzana; Procházka, David Anthony; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
This study attempts to assess how the online grocery supermarket environment impacts and alters the shopping behavior and buying habits of the online grocery customers. Based on the results of a qualitative research, this thesis identifies two different shopping strategies on the online grocery platform. The first strategy exhibits the same shopping behavior as in a traditional supermarket and is representative of those consumers who do not shop online for groceries regularly. The second shopping strategy, on the other hand, includes major alterations into the shopping habits and behaviors of online grocery shoppers. This strategy is common for shoppers who are regular visitors to the online supermarket and are therefore fully accustomed to the online grocery environment and its functions. Therefore, this research concludes that the online grocery shopping frequency and familiarity with the service are the main determinants of which strategy a consumer will adopt.
Vedoucí práce: Zuzana Chytková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses